Anoplasti untuk atresia ani tipe III dengan fistula yang disertai komplikasi megakolon pada anak anjing - Tanurahardja, Viviana Anyaputri; Wirata, I Wayan; Pemayun, I Gusti Agung Gde Putra (ARSHI Veterinary Letters, 2025)
Congenital anorectal malformations, including atresia ani, are uncommon conditions in small animals that cause gastrointestinal dysfunction. This case report describes the surgical management and outcomes of type III atresia ani in a juvenile dog. A one-month-old female mixed-breed puppy presented with severe tenesmus, progressive abdominal distension, and complete absence of normal faecal passage. Clinical examination identified an anal dimple lacking a functional opening, accompanied by a small ventral perineal fistula. Radiographic assessment confirmed type III atresia ani, characterised by a blind-ending rectal pouch located more than 1 cm cranial to the anal dimple and associated with marked megacolon. Surgical intervention was performed via anoplasty, combined with manual evacuation of the impacted faeces and temporary anal stenting using a 1-cc syringe port to maintain luminal patency. Postoperative management included broad-spectrum antibiotics, lactulose, analgesic therapy, and meticulous wound care. Although normal defaecation was restored, the patient developed tenesmus, incomplete evacuation, and faecal incontinence. These complications are associated with irreversible megacolon and anal sphincter dysfunction. Conservative therapy failed to achieve improvement, indicating the need for surgical intervention.